REINTERPRETASI IMAJINASI MASKULINITAS DARI PERSPEKTIF TEOLOGI KERAPUHAN - Kaseh, Novalin (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
This article aims to reinterpret the imagination of masculinity (Toxic Masculinity) with Theology of Vulnerability as the analytical tool. Focusing on the problem of suicide cases in the world which is still very worrying, including in Indonesia itself, this article argues that one of the reasons is because of this Masculinity Imagination. Quoting data from the World Health Organization (WHO) 2021 Global Health Estimates, of the 6,544 suicides across all ages in Indonesia, 5,095 cases occurred in men. The construction of men must not cry, must be strong, not weak, places them in an excessive imagination of "physical strength". The method used is a literature study using the framework of Vulnerability Theology in analyzing masculinity itself. As a result, fragility and vulnerability are a theology that must be celebrated, not shunned or discarded. Masculinity becomes a problem when it eliminates the femininity that exists in every human being. Masculinity must accept weakness, vulnerability, gentleness as a source of human communion with God.